Kleisin NSE4 of the SMC5/6 complex is necessary for DNA double strand break repair, but not for recovery from DNA damage in Physcomitrella (Physcomitrium patens) - Holá, Marcela; Vágnerová, Radka; Angelis, Karel J (Plant molecular biology, 2021)
Kleisin NSE4 and circular form of SMC5/6 is indispensable for DSB repair and necessary for gene targeting but is not enough for recovery of cells from DNA damage in Physcomitrella. Structural maintenance of chromosomes (SMC) complexes are involved in cohesion, condensation and maintenance of genome stability. Based on the sensitivity of mutants to genotoxic stress the SMC5/6 complex is thought to play a prominent role in DNA stabilization during repair by tethering DNA at the site of lesion by a heteroduplex of SMC5 and SMC6 encircled with non-SMC components NSE1, NSE3 and kleisin NSE4. In this study, we tested how formation of the SMC5/6 circular structure affects mutant sensitivity to DNA damage, kinetics of DSB repair and gene targeting. In the moss Physcomitrella (Physcomitrium patens), SMC6 and NSE4 are essential single copy genes and this is why we used blocking of transcription to reveal their mutated phenotype. Even slight reduction of transcript levels by dCas9 binding was enough to obtain stable lines with severe DSB repair defects and specific bleomycin sensitivity. We show that survival after bleomycin or MMS treatment fully depends on active SMC6, whereas attenuation of NSE4 has little or negligible effect. We conclude that circularization of SMC5/6 provided by the kleisin NSE4 is indispensable for the DSB repair, nevertheless there are other functions associated with the SMC5/6 complex, which are critical to survive DNA damage.
Keywords: DNA Damage; sekvence aminokyselin; Gene targeting; Gene Expression Regulation, Plant; Comet assay; genotyp; Physcomitrella; NSE4 kleisin; Genotype; poškození DNA; mutace; dvouřetězcové zlomy DNA; Cell Cycle Proteins; DNA, Plant; rostlinné proteiny; polymerázová řetězová reakce s reverzní transkripcí; proteiny buněčného cyklu; DNA repair; Mutation; Bryopsida; Amino Acid Sequence; mechy; oprava DNA; DNA Breaks, Double-Stranded; DNA rostlinná; regulace genové exprese u rostlin; fylogeneze; Plant Proteins; multiproteinové komplexy; Reverse Transcriptase Polymerase Chain Reaction; dCas9; Multiprotein Complexes; DNA Repair; Physcomitrium patens; sekvenční homologie aminokyselin; Phylogeny; Sequence Homology, Amino Acid; SMC5/6 complex